THE INFLUENCE OF PRICE PROMOTIONS ON THE ELEMENTS OF CONSUMER BRAND EQUITY: a study of an unfamiliar brand in the Russian brandy market - Raevskaya, Ekaterina (My University, 2014)
It is commonly believed that price promotions are effective only for the short-term sales generation, whilst in the long run they lead to the brand destruction. Previous literature suggests price promotions reduce perceived quality of the brand and brand associations and in the end result in decreased brand equity. However, the latest ban on alcohol advertising has left Russian alcohol market with price promotions as one of the main alternative elements of the promotional strategy. This has made the companies to reconsider price promotions as a possible mean of strategic communication. To address this problem the present study analyses the influence of price promotion on brand awareness, perceived quality and brand associations of an unfamiliar brandy brand in the Russian market and the possible moderating effects of the brand type and consumer psychographic characteristics. The results are based on a field experiment held within 1 month in an alcohol specialty supermarket. To detect the effect of price promotion, consumer surveys were held in the pre- and post-promotion periods. The findings have shown increase in brand awareness and no changes in perceived quality and brand associations in the subsample aware of the latest promotion suggesting the importance of informing the consumes about the upcoming sales promotions. Brand awareness has proved to be positively associated to both perceived quality and brand associations suggesting that the first step to enhance brand equity is to increase brand awareness. In addition, the nature of the product and brand equity was found to moderate the effect of price promotion on the brand equity. The results have shown that the absence of benefit congruency effect between price promotion and hedonic low equity brand does not have negative influence on the market share. However, it was not possible to check moderating influence of consumer psychographic characteristics on perceived quality and brand associations due to the absence of changes in these elements of brand equity. Nevertheless, the results of the research suggest that consumer psychographic characteristics are defined by the conditions of the local market.
Keywords: price promotion; brand equity dimensions; Russian brandy market; fi=Master's Degree Programme in International Business|